22 Renewal of conjunctival epithelium over amniotic membrane to perform autologous simple conjunctival epithelial transplantation (SCET): in vitro validation and results of clinical application for primary pterygium. (16th November 2022) - Bertolin, Marina; Pedrotti, Emilio; Bonacci, Erika; Bosello, Francesca; Barbaro, Vanessa; Breda, Claudia; Ponzin, Diego; Marchini, Giorgio; Fasolo, Adriano
Abstract : Background: Transplantation of ex vivo cultured conjunctival cell layers, generated on amniotic membrane or other scaffolds, provides a viable option in treating heterogeneous ocular surface conditions. By comparison, cell therapy is costly, labour-intensive and subject to good manufacturing practice requirements and regulatory approval; no conjunctival cell-based therapy is currently available. Several techniques are available after primary pterygium excision to recover the ocular surface anatomy by restoring healthy conjunctival epithelium and preventing recurrence and complications. However, application of conjunctival free autograft or transpositional flap to cover the bared scleral area is limited when the conjunctiva are to be spared for future glaucoma filtering surgery, in patients with large or double-headed pterygia, in recurrent pterygia, or when the harvesting of donor conjunctival is precluded by scarring. Aim: To develop a simple technique to obtain expansion of the conjunctival epithelium when applied in vivo in diseased eyes. Methods: We evaluated in vitro the best way of gluing conjunctival fragments over the AM, the efficiency of the fragments to generate conjunctival cell outgrowths, the molecular marker expression, and the feasibility of shipping preloaded AM. We performed simple conjunctival epithelial transplantation (SCET) in which we glued an amniotic membrane patch pre-loaded with autologous conjunctival tissue fragments over the scleral defect after pterygium excision and evaluated the recovery of the normal conjunctival epithelium and the disease recurrence up to 12 months after surgery. Results: 65-80% of fragments generated outgrowth 48-72h after gluing, without differences between type of AM preparation and fragment size. Within 6-13 days, a full epithelium covered the surface of the amniotic membrane. Specific marker expression (Muc1, K19, K13, p63, ZO-1) was detected. The shipping test showed after 24h the 31% of the fragments glued over the AM epithelial side, compared to more than 90% of fragments stayed attached in the remaining conditions (stromal side, stromal without spongy layer, epithelial side without epithelium). Surgical excision and SCET for nasal primary pterygium were performed in 6 eyes/patients. No graft detachment and recurrence occurred within 12 months. In vivo confocal microscopy showed progressive expansion of the conjunctival cell population and formation of a clear cornea-conjunctiva transition. Conclusions: We established the most suitable conditions for a novel strategy based on in vivo expansion of conjunctival cells from conjunctival fragments glued over the AM. The application of SCET seems to be effective and replicable for the renewal of conjunctiva in patients requiring ocular surface reconstruction.